PENINGKATAN KOMPETENSI PESERTA PELATIHAN MELALUI PENGGUNAAN PEMBELAJARAN BERBASIS MASALAH - Atiyah Suharti (Balai Diklat Keagamaan Bandung, 2020)
This research uses descriptive research and is carried out in the training to strengthening headmaster’s competency. The research is held on two subject matters: teachers’ supervision and education personnel. The main objective of this study is to determine competency improvement by using problem-solving based worksheets. The subjects were training participants. The study was conducted in 2020. The result shows the value of increased competence is 72.15%. This study concludes that the application of using worksheets based on problem solving can improve training participants’ competence. In addition, the application of this learning approach increases both participation and activities of the participants during the learning process in adults.Keywords: competence; problem solving based learning